Study of concrete thermal colour and strength correlation using image generated by infrared thermography (IRT) - Ridzwan, Mazlan (2017)
Infrared thermography (IRT) is a powerful device to examine structural condition and similarly useful for damage valuation. It is a non-contact and non-destructive method that permits fast investigations. Extremely efficient infrared cameras and versatile software have simplified thermography significantly over the years. While IRT has broad applications in process industries, it is not yet extensively implemented in the investigation of buildings.The purpose of this study is to investigate the behaviour of thermal colour of an image generated by the infrared thermography camera (IRT) from under stressed concrete cube and correlate the colour pattern with the strength of the various concrete grade. Compressive strength test were made using a universal test machine. During the compressive test, thermal image will be capture by the IRT and will be analysed with Colour Detector based on ImageJ IRT Analysis Software. The software used to detect the RGB colour of thermal image and produce set of data of different value to be analysed and compared. The size of the concrete cube is 150mm X 150 mm. The test involve concrete cube of grade 25, grade 30, grade 35, grade 40, grade 45, and grade 50.Each of grade will come in 3 cube and the total cube 18 cubes are prepared to get the average results of the compressive test. Every changes of colour due to the load apply and difference grade of concrete will be recorded. Test was performed in the lab to have more quality image. From this research, the result shown a positive according to the objectives. It can be conclude that higher grade of concrete generates higher value of RGB in thermal image as it being analysed using the ImageJ software.In addition, there is a difference in thermal RGB colour pattern produce by the thermal image from IRT due to load applied of 450 kN in every grade of concrete cube. The equation generates from the correlation of RGB value and concrete grade can be applied in finding the concrete grade in further studies.